Knowledge, attitude and practices of upright birthing positions in women from semi-urban and rural areas of Raigad district, Maharashtra: a cross-sectional study - Prerna Kokane; Bela Agrawal; Ramandeep Kaur Saini; Madhulika Singh; Ishika Rakesh Kohli; Anushka Govardhan Koli; Lata Kumari; Sushil Kumar; Esakidas Konar (International Journal Of Community Medicine And Public Health, 2026)
Background: Maternal-mobility and choice of birthing-position are important components of respectful maternity-care that influence labor-experience and birth-outcomes. Despite growing evidence supporting the use of upright-birthing positions, gap exists about women’s awareness and actual use of different-positions during childbirth. This study aimed to assess the knowledge, attitudes, and practices related to birthing-positions among women of Raigad-district, Maharashtra. Methods: A community-based cross-sectional-study was conducted among 786 women aged 15-49 years from rural and semi-urban-areas. Data were collected using validated-structured-questionnaire. A standardized-information-booklet containing pictorial-representations of various birthing-positions was used solely to facilitate uniform identification of positions during interviews. Descriptive-statistics were used to summarize participant’s knowledge, perceptions and reported practices. Results: Awareness of both upright and horizontal birthing-positions was reported by 91% of women in semi-urban areas and 67% of women in rural-areas. However, participants across both settings indicated that they were not offered a choice of birthing-position during labour. During first-stage of labour, dorsal-supine-position was most commonly reported in semi-urban (49%) and rural (32%) women. In the second stage, dorsal-supine remained the predominant-position reported by 54% of semi-urban and 60% of rural-participants. Squatting was the most frequently reported upright-position during second-stage (19% semi-urban and 35% rural women). Dorsal-supine, lithotomy and squatting-positions were commonly perceived as safe-options for childbirth. Conclusions: Although knowledge of various birthing positions was relatively high, women reported limited-autonomy in choosing their preferred-position during labour. The findings highlight a gap between awareness and practice hence emphasize the need for greater promotion of informed-choice, provider-education and woman-centred maternity care to support the safe use of multiple-birthing positions.